The impact of Kiasu mindset on students’ achievement goal orientations and learning strategies in Singapore - CHOI, Haelim (Institutional Knowledge at Singapore Management University, 2021)
Kiasuism, defined as the fear of losing out, has been a well-known and widespread phenomenon in Singapore. Despite the long history of Kiasuism in Singaporeans, there has been a dearth of research in this topic. The current research investigated the influence of the Kiasu mindset on Singaporean students’ achievement goal orientation and learning strategy, and also explored the impact of social comparison as a moderator. Study 1 showed initial evidence of a positive relationship between Kiasu mindset and performance goal orientations (i.e., approach and avoidance). Study 2 replicated this finding and further revealed a positive association of Kiasu mindset with surface learning. The moderated mediation model was also shown to be significant: performance goal orientations mediated the relationship between Kiasu mindset and surface learning, and this mediating relationship was moderated by social comparison. Specifically, Kiasu mindset was related to high performance-avoidance goal orientation, and the performance-avoidance goal orientation was associated with higher surface learning only under downward social comparison. In addition, Kiasu mindset was also associated with high performance-approach goal orientation, and this goal orientation was negatively associated with surface learning only under upward social comparison. Taken together, the paper yields multiple theoretical and practical implications.